Marcelego z Ancyry interpretacja Prz 8,22-30 - Słomka, Jan (Śląskie Studia Historyczno-Teologiczne, 2011)
Prov 8:22-30 is one of the key Bible texts for the Arian controversy. The words “made” and “begets”, used for describing the origin of Wisdom in the Septuagint, became a significant argument for the theory of the creation of the Logos in Arius’ doctrine. According to Arius, the text refers to the fact that Logos was begotten or, in other words, created before the creation of the world. In his polemic with Arius, Athanasius made a difference between the meanings of the two words: according to him, “begets” referred to the Logos being born of God before the ages, while the word “created” referred to the Incarnation. Marcellus, an anti-Arian polemist and Athanasius’ follower, took a different route. He claimed that both words had an identical meaning, however, they did not refer to the pre-eternal birth – creation, but to the moment of the Incarnation, the creation of the body the Logos took on. Marcellus did not acknowledge the concept of birth from God, and that assumption led him to apply some elements of Origen’s allegorical exegesis in his own exegesis of the discussed text, though he considered Origen as a major heretic.